Financial innovations and their role in the modern financial system-identification and systematization of the problem - Joanna Błach (e-Finanse: Financial Internet Quarterly, 2011)
This paper discusses the role that financial innovations play in the modern financial system, aiming at identifying and systematizing the core problems and definitions related to this issue. The paper first describes the importance of the financial system and financial markets in the economy, explaining their functions and presenting their particular characteristics, focusing on their innovativeness. Then, based on the theoretical studies, the broad definition of the financial innovations is developed, stating that any new developments in any elements of the financial system, including: markets, institutions, instruments and regulations, can be regarded as financial innovations if they are perceived as new by the end-user of innovation. Next, the systematization of the most important types of financial innovations is presented regarding different classification criteria, such as: sources of innovations, motives for innovations, their effects or functions. As financial innovations are not a homogenous group of financial developments, their implications for the financial system can be ambiguous, thus the final assessment of their role can not be generalized and should be made on a case-by-case basis. The information presented in this paper can be regarded as an introduction, encouraging to do further research, as the complexity of the financial innovations makes them an interesting and important subject for this.
Keywords: G10; O31; 330; financial system; financial market; financial innovations